Digital compositing for film and video - Wright, Steve (Oxford, UK : Focal, 2010)
This practical, hands-on guide addresses the problems and difficult choices that professional compositors face on a daily basis. You are presented with tips, techniques, and solutions for dealing with badly shot elements, color artifacts, mismatched lighting and other commonly faced compositing obstacles. Practical, in-depth lessons are featured for bluescreen matte extraction, despill operations, compositing operations, as well as color-corrections. The book is presented entirely in an application-agnostic manner, allowing you to apply lessons learned to your compositing regardless of the software application you are using.
Previous ed.: 2006. Includes index. Includes 1 CD.
MA
Keywords: Video recording; Cinematography -- Special effects; Image processing -- Digital techniques; Trick cinematography